2022
DOI: 10.1111/caje.12586
|View full text |Cite
|
Sign up to set email alerts
|

The role of non‐discrimination in a world of discriminatory preferential trade agreements

Abstract: In a three‐country model of endogenous trade agreements, we study the implications of the most‐favoured‐nation (MFN) clause when countries are free to form discriminatory preferential trade agreements (PTAs). Under current rules of the World Trade Organization (WTO), although non‐member countries face discrimination at the hands of PTA members, they themselves are obligated to abide by MFN and treat PTA members in a non‐discriminatory fashion. The non‐discrimination constraint of MFN reduces the potency of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In the second one, the South would prefer keeping the low institutional quality, if the trade agreement were not enforcing the institutional improvement (black region). This challenges the view held by many that even in the absence of binding contracts trade will provide sufficient incentives for developing countries to improve institutional quality in their self-interest (see Rodrik, 2002;IMF, 2005, for a discussion).…”
Section: Making Use Of Vmentioning
confidence: 95%
“…In the second one, the South would prefer keeping the low institutional quality, if the trade agreement were not enforcing the institutional improvement (black region). This challenges the view held by many that even in the absence of binding contracts trade will provide sufficient incentives for developing countries to improve institutional quality in their self-interest (see Rodrik, 2002;IMF, 2005, for a discussion).…”
Section: Making Use Of Vmentioning
confidence: 95%
“…We consider a model with three countries, 𝒩={S,T,R}, where the third country R$$ R $$ captures rest‐of‐the‐world. We adapt a “pure endowments” trade model developed by Saggi et al (2022). There are three goods, corresponding to the three countries, represented in lowercase letters as false{s,t,rfalse}$$ \left\{s,t,r\right\} $$.…”
Section: The Modelmentioning
confidence: 99%
“…Recently, Saggi et al. (2022) explored the implications of MFN clauses when countries were free to form discriminatory preferential trade agreements. Although these studies offer interesting results in terms of importing trade policies, their purposes and models differ substantially from ours.…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that a move from bilateral or regional trade agreements to the MFN treatment may benefit developing countries but the effect may be small when tariffs are set non-cooperatively. Recently, Saggi et al (2022) explored the implications of MFN clauses when countries were free to form discriminatory preferential trade agreements. Although these studies offer interesting results in terms of importing trade policies, their purposes and models differ substantially from ours.…”
mentioning
confidence: 99%